Exploring Register Variation in Korean Popular Music (K-Pop) - Asfi Aniuranti (Universitas Ahmad Dahlan, 2019)
Register is an interesting part of language varieties examined in sociolinguistics. This study investigates one of register features namely English terms in Korean Popular Music (K-Pop). The topic is chosen due to the high number of English terms (at least 105 terms) and the difficulties in understanding their meanings. The objectives of this study are (1) describing the form of the terms, (2) describing the formation of the terms, and (3) explaining the specificity of the meanings. This study was conducted through several phases called data gathering, data analysis and presentation of data analysis. Overall, the results reveal several prominent findings. First, most of the terms are in a form of words, meanwhile, the terms in phrases are limited. Second, there are several types of term manufacturing, and the most dominant one is compounding. Third, most of the terms’ meanings have been changed from the meanings on the dictionary, and they are classified as semantic narrowing.